Building climate-resilient agricultural systems for a sustainable future of food, land and water - Kumar, Sunil; Ghasal, Prakash Chand (Indian Farming, 2025)
Climate change presents significant challenges to global food, land, and water systems, with agriculture both contributing to emissions and vulnerable to climate impacts. Integrated farming systems (IFS) and climate-smart agriculture (CSA) provide solutions by enhancing productivity, resilience, and sustainability. IFS optimizes resource use by integrating crops, livestock, aquaculture, and agroforestry, while CSA focuses on practices like precision agriculture, water-efficient techniques, and soil carbon sequestration to adapt to climate change. Organic and natural farming reduce reliance on synthetic inputs, promote soil health, and enhance biodiversity. Transforming agricultural systems requires supportive policies, research, capacity building, and global collaboration. By adopting these approaches, agriculture can adapt to climate change, mitigate its effects, and ensure food security, contributing to global sustainability goals and building a resilient future for food, land, and water systems.